Innovative teaching modules utilizing discovery learning to strengthen mathematical problem-solving skills - Syifa Ismayanti; Iik Nurhikmayati; Mohamad Gilar Jatisunda (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This research aims to strengthen students' mathematical problem-solving skills by creating teaching modules based on the Discovery Learning approach. Because traditional teaching approaches often fail to engage students effectively, the development of this module is essential. In our research, we use research and development (R&D) techniques with 4D models up to the Development stage, which concentrates on module design and testing. Based on the findings of the validity test, media experts got a score of 73%, while material experts got a score of 87%. The criteria used include relevance, completeness, ease of understanding, suitability for discovery learning, and problem-solving skills. Meanwhile, practicality received an average score of 93.5% from teachers and students. Therefore, modules can be considered legitimate and useful, and are expected to improve student engagement and problem-solving skills. Through this research, it is hoped to significantly advance mathematics education with the creation of more creative teaching strategies. The findings provide a foundation for future studies to refine and expand Discovery Learning-based instructional materials in mathematics education.